1992
DOI: 10.1084/jem.176.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin is a subunit of nitric oxide synthase from macrophages.

Abstract: SummaryA central issue in nitric oxide (NO) research is to understand how NO can act in some settings as a servoregulator and in others as a cytotoxin. To answer this, we have sought a molecular basis for the differential regulation of the two known types of NO synthase (NOS). Constitutive NOS's in endothelium and neurons are activated by agonist-induced elevation of Ca 2+ and resultant binding of calmodulin (CaM). In contrast, NOS in macrophages does not require added Ca 2+ or CaM, but is regulated instead by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
234
1
5

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(249 citation statements)
references
References 31 publications
6
234
1
5
Order By: Relevance
“…This calmodulin independence was confirmed by the molecular cloning and sequence determination of murine macrophage NO synthase cDNA [8]. However, more recent studies on the structure of murine macrophage NO synthase cDNA suggests the presence of a putative calmodulin-binding site for the enzyme [lo] and this is consistent with the finding that calmodulin could be a subunit of the macrophage NO synthase [13]. We also have identified and purified an inducible calmodulindependent NO synthase in the liver of rats treated with Prupionibncterium acnes and Escherichia coli lipopolysaccharide (LPS) [14, 151. To obtain more information on the biological roles of inducible NO synthase(s) and the moleciilar basis of control of their enzymic activity and gene expression, we have cloned a cDNA for the inducible N O synthasc from rat liver.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…This calmodulin independence was confirmed by the molecular cloning and sequence determination of murine macrophage NO synthase cDNA [8]. However, more recent studies on the structure of murine macrophage NO synthase cDNA suggests the presence of a putative calmodulin-binding site for the enzyme [lo] and this is consistent with the finding that calmodulin could be a subunit of the macrophage NO synthase [13]. We also have identified and purified an inducible calmodulindependent NO synthase in the liver of rats treated with Prupionibncterium acnes and Escherichia coli lipopolysaccharide (LPS) [14, 151. To obtain more information on the biological roles of inducible NO synthase(s) and the moleciilar basis of control of their enzymic activity and gene expression, we have cloned a cDNA for the inducible N O synthasc from rat liver.…”
supporting
confidence: 76%
“…Recently, Cho et al [13] found that calmodulin-dependent NO synthase is also strongly induced in murine macrophage-like cell lines. RAW 264.7, by treatment with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…This isoform is not typically expressed in the cellular resting state (exceptions include intestinal and bronchial epithelial cells, and renal tubular epithelial cells. [6,7] Instead, gene transcription is activated under acute inflammatory or stress conditions, and because calmodulin binds to iNOS in the absence of calcium elevations, [10] the enzyme produces NO in large quantities in a sustained manner. Pro-inflammatory cytokines, microbial products, and oxidative stress are all particularly effective at stimulating iNOS transcription.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal oxygenase domain of NOS contains one mole equivalent of haem and possesses binding sites for L-arginine and (6R)-5,6,7,8-tetrahydrobiopterin (BH % [12]). The reductase and oxygenase domains are linked by a calmodulin (CaM) binding sequence [8,13,14] ; CaM binding facilitates electron transfer from the reductase to the oxygenase domain [15] and is proposed also to enhance the rate of interflavin electron transfer [16][17][18]. Of the three NOS isoforms, the inducible NOS (iNOS) isoform is expressed with CaM tightly bound [13] and regulation of activity is primarily through transcriptional processes ; the activities of endothelial NOS (eNOS) and neuronal NOS (nNOS) are regulated by CaM Abbreviations used : BH 4 , (6R)-5,6,7,8-tetrahydro-L-biopterin ; CaM, calmodulin ; CPR, cytochrome P450 reductase ; NOS, nitric oxide synthase ; eNOS, endothelial NOS ; FAD hq , hydroquinone FAD ; FAD sq semiquinone FAD ; FMN ox , oxidized FMN ; FMN sq , semiquinone FMN ; iNOS, inducible NOS ; nNOS, neuronal NOS ; nNOS CaM + , nNOS reductase complexed with CaM ; nNOS CaM − , nNOS reductase in which CaM has been removed by treatment with EDTA.…”
Section: Introductionmentioning
confidence: 99%